Size of Training Firms and Cumulated Long-run Unemployment Exposure – The Role of Firms, Luck, and Ability in Young Workers' Careers - Steffen Müller; Renate Neubäumer (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
This paper analyzes how life-cycle unemployment of former apprentices depends on the size of the training firm. We start from the hypotheses that the size of training firms reduces long-run cumulated unemployment exposure, e.g. via differences in training quality and in the availability of internal labor markets, and that the access to large training firms depends positively on young workers' ability and their luck to live in a region with many large and medium-sized training firms. We test these hypotheses empirically by using a large administrative data set for Germany and find corroborative evidence.
urn:nbn:de:gbv:3:2-53163
Keywords: D21; L10; L25; L26; L29; M13; 330; unemployment; training; apprenticeship; young workers; mobility; firm size